Millennial Generation Motivation, Market Activity, and Business Development on Cyber Public Relations-based Stock Investment - Nahriana (International Journal of Asian Business and Management, 2023)
This study aims to determine: a) what factors influence the millennial generation to invest in shares based on Cyber ​​Public Relations; b) what actions investors take when share prices fall during a period of pandemic disease; and c) how to expand the reach of stock investment during a pandemic disease by using cyber public relations. Investors who invest based on Cyber ​​Public Relations become the research sample. Non-probability sampling in the form of incidental sampling was used in this study. Researchers used qualitative techniques in this research method. The data analysis strategy used in this research is analytical technique, especially data coding and critical hermeneutic analysis. First, motivation has a significant and beneficial effect on investment interest, according to the findings. A person's interest in investing will increase if motivated or encouraged to do so. Second, the use of Cyber ​​Public Relations-based stock investments makes it easier for respondents to invest. Third, when making decisions about stock losses, it is necessary to consider the future